Desain Karakter dalam Buku Ilustrasi sebagai Edukasi Resiko Overthinking bagi Remaja 18-22 Tahun - Dea Salfia Murdiasari; Aninditya Daniar; Diana Aqidatun Nisa (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
Overthinking is a state where a person thinks about something excessively or spends a lot of time thinking and analyzing something. Overthinking has been known for a long time, but the term "overthinking" has only recently emerged and is being recognized by the public, especially among adolescents. Overthinking is not a mental health disorder, but it is one of the triggers for mental disorders. Overthinking that is continuously experienced by a person will result in various impacts, one of which is anxiety. Previous research states that many of today's Indonesian adolescents aged 16-24 years are prone to anxiety disorders. Another impact of overthinking can cause stress or mild or severe psychological disorders. So that an appropriate media is needed and can be used as a medium for adolescent education, especially for late adolescents aged 18-22 years, which has an impact during the transition from childhood to adulthood, where adolescents have emotions that are still unstable and easily influenced by their surroundings so that they are prone to overthinking. The use of primary and secondary data through qualitative data analysis is used as a reference and support for the design of this book. And with the creation of educational media in the form of illustrated books about the risks of overthinking, it is hoped that it can be an easy educational media to raise awareness of the impact of overthinking that has a negative impact on physical and mental health.